2023
DOI: 10.1007/s13402-022-00766-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor ratio of unsaturated to saturated sulfatide species is associated with disease-free survival in intrahepatic cholangiocarcinoma

Abstract: Purpose Cholangiocarcinoma (CCA) is a malignancy arising from the bile duct epithelium and has a poor outcome. Sulfatides are lipid components of lipid rafts, and are implicated in several cancer types. In the liver, sulfatides are specifically present in the bile ducts. Here, sulfatide abundance and composition were analyzed using mass spectrometry imaging in intrahepatic CCA (iCCA) tumor tissue, and correlated with tumor biology and clinical outcomes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The number of studies reported for each cancer type is as follows (Fig. 4 a): there were six studies (16%) each on colorectal [ 24 – 29 ] and prostate cancer [ 30 – 35 ], five (13%) on breast cancer [ 36 – 40 ], three (8%) each on lung [ 41 43 ] and ovarian cancer [ 44 – 46 ], two (5%) on bladder cancer [ 47 , 48 ], intrahepatic cholangiocarcinoma [ 49 , 50 ], pancreatic cancer [ 51 , 52 ], and renal cell carcinoma [ 53 , 54 ], one (3%) each from cervical cancer [ 55 ], chordoma [ 56 ], endometrial cancer [ 57 ], liver cancer [ 58 ], malignant mesothelioma [ 59 ], nasopharyngeal carcinoma [ 60 ], and oral cancer [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of studies reported for each cancer type is as follows (Fig. 4 a): there were six studies (16%) each on colorectal [ 24 – 29 ] and prostate cancer [ 30 – 35 ], five (13%) on breast cancer [ 36 – 40 ], three (8%) each on lung [ 41 43 ] and ovarian cancer [ 44 – 46 ], two (5%) on bladder cancer [ 47 , 48 ], intrahepatic cholangiocarcinoma [ 49 , 50 ], pancreatic cancer [ 51 , 52 ], and renal cell carcinoma [ 53 , 54 ], one (3%) each from cervical cancer [ 55 ], chordoma [ 56 ], endometrial cancer [ 57 ], liver cancer [ 58 ], malignant mesothelioma [ 59 ], nasopharyngeal carcinoma [ 60 ], and oral cancer [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The number of studies reported for each country is as follows (Fig. 4 b): 10 studies (26%) were reported from China [ 24 , 26 , 28 , 45 , 46 , 50 , 52 , 55 , 59 , 60 ], eight (21%) from Japan [ 31 , 37 – 39 , 41 43 , 53 ], four (11%) from the USA [ 30 , 33 , 47 , 48 ], two (5%) each from Australia [ 32 , 34 ], Brazil [ 29 , 61 ], and Germany [ 25 , 40 ], one (3%) each from Argentina [ 54 ], Canada [ 57 ], Czech [ 51 ], Finland [ 44 ], Italy [ 56 ], Netherlands [ 49 ], Portugal [ 36 ], Romania [ 27 ], Singapore [ 58 ], and Spain [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of sulfatides are generally elevated in colorectal, ovarian, or renal carcinoma ( Jirásko et al, 2022 ) and intrahepatic cholangiocarcinoma ( Huizing et al, 2023 ). Sulfatides are often elevated in hepatocellular carcinma (HCC) ( Takahashi and Suzuki, 2012 ), and previous studies have shown that sulfatides are promoters of cell adhesion and metastasis in HCC ( Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%